Effect of different abutments and connections in deformation crestal bone - Mesquita, Alfredo Mikail Melo; Silva, Juliano H.M.; Saraceni, Cintia Helena Cury; Kojima, Alberto N. [UNESP]; Özcan, Mutlu (Wolters Kluwer, 2016)
Statement of Problem: The use of Morse taper connections is increasing, but little is known about the biomechanical use of abutments and their use in fixed prostheses. Purpose: This study evaluated the transmission of load on the bone implant-supported dentures, varying the type of prosthetic connection and abutment. Material and Methods: Using 4 polyurethane models, 3 implants were inserted into each block, establishing the following groups: (a) external hexagon and Micro-Unit abutments; (b) external hexagon and UCLA abutment; (c) Morse taper and Micro-Unit abutments; and (d) Morse taper and UCLA abutments. The prosthetic structures were cast, and in a universal testing machine, load was applied midway between the implants, with cantilever intervals of 5, 10, 15, 20, and 25 mm. Data were analyzed by Mann-Whitney, Friedman, and Kruskal-Wallis tests (P < 0.05). Results: Regarding the prosthetic connection, there was no difference in the use of hexagonal or Morse taper, but the use of Micro- Unit abutment showed lower deformation values than UCLA for the 2 connections. Conclusions: The use of intermediate abutments affects the distribution of masticatory loads: the greater the length of the cantilever, the greater the surface deformation of the bone around the distal implant.
Keywords: Biomechanics; Dental implant; Implantsupported prostheses; Strain gauges